2011
DOI: 10.1093/toxsci/kfr262
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomic and Genomic Analyses of TCDD-Elicited Metabolic Disruption in Mouse and Rat Liver

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) elicits a broad spectrum of species-specific effects that have not yet been fully characterized. This study compares the temporal effects of TCDD on hepatic aqueous and lipid metabolite extracts from immature ovariectomized C57BL/6 mice and Sprague-Dawley rats using gas chromatography-mass spectrometry and nuclear magnetic resonance-based metabolomic approaches and integrates published gene expression data to identify species-specific pathways affected by treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 51 publications
10
66
0
Order By: Relevance
“…Despite similarities in structural organization, amino acid sequence, and mode of action, as well as the conserved specificity of AhR binding to DREs (Bank et al, 1992; Denison et al, 1986, 2011; Hahn et al, 1997; Okey et al, 1994), a number of species-specific toxicogenomic, histopathological, and physiological responses are elicited by TCDD and related compounds (Black et al, 2012; Boutros et al, 2008; Boverhof et al, 2006; Carlson et al, 2009; Dere et al, 2011b; Forgacs et al, 2012, submitted for publication; Gonzalez and Shah, 2008; Maglich et al, 2002; Poland and Knutson, 1982; Silkworth et al, 2005). For example, acute high dose TCDD exposure induces hepatic steatosis in the mouse, with minimal hepatic fat accumulation in rats, while hepatocyte hyper-trophy is only reported in rat (Boverhof et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite similarities in structural organization, amino acid sequence, and mode of action, as well as the conserved specificity of AhR binding to DREs (Bank et al, 1992; Denison et al, 1986, 2011; Hahn et al, 1997; Okey et al, 1994), a number of species-specific toxicogenomic, histopathological, and physiological responses are elicited by TCDD and related compounds (Black et al, 2012; Boutros et al, 2008; Boverhof et al, 2006; Carlson et al, 2009; Dere et al, 2011b; Forgacs et al, 2012, submitted for publication; Gonzalez and Shah, 2008; Maglich et al, 2002; Poland and Knutson, 1982; Silkworth et al, 2005). For example, acute high dose TCDD exposure induces hepatic steatosis in the mouse, with minimal hepatic fat accumulation in rats, while hepatocyte hyper-trophy is only reported in rat (Boverhof et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, acute high dose TCDD exposure induces hepatic steatosis in the mouse, with minimal hepatic fat accumulation in rats, while hepatocyte hyper-trophy is only reported in rat (Boverhof et al, 2006). Species-specific differences in choline metabolism (Forgacs et al, 2012) and serum clinical chemistry responses including alterations in serum alanine aminotransferase, cholesterol, free fatty acids, and triglycerides have also been reported (Boverhof et al, 2006; Forgacs et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several toxicological studies of environmental contaminants have reported the metabolomic effects of BDE-209-like compounds (e.g., dioxins, PCBs, and organohalogen pesticides). Acylcarnitines, phospholipids, fatty acids, and some amino acids were reported as potential biomarkers of exposure to these compounds, which were related to amino acid and lipid metabolism (Lin et al, 2011;Forgacs et al, 2012;O'Kane et al, 2013;Moser et al, 2015). In the aryl hydrocarbon receptor (AhR) null mouse, 2,3,7,8-tetrachlorodibenzofuran (TCDF) treatment did not induce significant changes in glucose and lipid metabolite profiles from serum and liver extracts, indicating that the induced metabolic changes of these pathways by dioxin-like compounds might be mediated by AhR expression (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, likely that such a change in metabolome is directly linked to the toxicity. To address this issue, many researchers have conducted comprehensive metabolomic analyses, the results of which have suggested that dioxins alter the levels of a number of compounds and components in the liver, [10][11][12] skeletal muscle, 12) hippocampus, 13) cerebellum, 14) blood, 15,16) and urine 17) in mice and rats, and in HepG2 cells. 18) However, in spite of these research findings, the component(s) contributing to dioxin toxicity appears to remain largely unidentified.…”
mentioning
confidence: 99%